Sé come un altro: l’etica della reciprocità nel pensiero di Paul Ricoeur - Sacchetti, Francesca (SocietàMutamentoPolitica, 2012)
Within the phenomenological view, the project of Paul Ricoeur is configured as a “way out” compared to the aporias in which Husserl’s phenomenology falls in his attempt to gain access to “other than itself” starting from transcendental solipsism. Analogical understanding, based on appresentational mechanism, gives way in Ricoeur’s thought to a practical philosophy in Kantian style, founded on respect, where otherness is a constituent dimension of subjectivity. In the paper firstly it is analyzed the general critique that Ricoeur moves to Husserlian idealism, while later it is highlighted how Ricoeur’s transition from phenomenology to hermeneutics involves a significant change in approaching and solving the problem of intersubjectivity. Finally, it appears clear that, from the very beginning, Ricoeur’s path is marked and driven by a strong ethical strain.